A comparison of the effects of Stevia extract and metformin on metabolic syndrome indices in rats fed with a high‐fat, high‐sucrose diet. Issue 8 (1st June 2020) - Ranjbar, Tahereh; Nekooeian, Ali Akbar; Tanideh, Nader; Koohi‐Hosseinabadi, Omid; Masoumi, Seyed Jalil; Amanat, Sasan; Azarpira, Negar; Monabati, Ahmad
Abstract: The beneficial effects of Stevia on metabolic indices have been studied in recent years. However, controversial results emphasize the need for further investigation. We aimed to examine and compare the effects of Stevia's hydroalcoholic extract with two dosages (200, 400 mg/kg) with those of metformin (100 mg/kg) on metabolic syndrome (MetS) indices of rats fed with a high‐fat, high‐sucrose diet (HFHS). It was found that both Stevia extract and metformin could prevent the adverse effects of a HFHS on lipid profile, liver enzymes, total antioxidant capacity (TAC), and histopathologic factors. Except for the finding that metformin showed a greater potential to alleviate insulin resistance than did Stevia extract, no significant difference was observed between the rats receiving metformin or Stevia extract. In addition, using a high treatment dosage of Stevia extract did not lead to better results than a low dosage. Collectively, the efficacy of Stevia extracts to modify metabolic, oxidative, and histopathological indices in a MetS model was comparable to that of the metformin. Practical applications: This study was aimed to compare the efficiency of Stevia hydroalcoholic extract with metformin in attenuating MetS abnormalities of rats induced by a high‐fat, high‐sucrose diet. The results showed the beneficial changes caused due to the administration of Stevia extract on lipid profile, antioxidant capacity, liver enzyme, and liver histopathological indices. The changes were comparable with the results of metformin group. Despite some promising results, further investigation is suggested to evaluate the effectiveness of Stevia extract on human subjects. Abstract : This study was aimed to compare the efficiency of stevia hydroalcoholic extract with metformin in attenuating metabolic syndrome abnormalities of rats induced by a high‐fat high‐sucrose diet. The results showed the beneficial changes caused due to the administration of Stevia extract on lipid profile, antioxidant capacity, liver enzyme and liver histopathological indices. The changes were comparable with the results of metformin group. Despite some promising results, further investigation is suggested to evaluate the effectiveness of Stevia extract on human subjects.